2017
DOI: 10.1021/acs.langmuir.7b00704
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Spreading of a Drop upon Impact onto a Surface

Abstract: Study of the spreading of an impacting drop onto a surface has gained importance recently due to applications in printing, coating, and icing. Limited studies are conducted to understand asymmetric spreading of a drop seen upon drop impact onto a moving surface; there is no relation to describe such spreading. Here, we experimentally studied the spreading of a drop over a moving surface; such study also provides insights for systems where a drop impacts at an angle relative to a surface, i.e., drop has both no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…However, the modification of the wetting dynamics by movement is reflected in the higher Weber number regime (We = 25.6). It can also be observed that the spreading and receding phases of the lamella were thinner downstream at a given time (see the right side of the dotted lines in Figure 3b and 3c), which corresponds reasonably well with the findings of previous studies 22,24 . No distinguishable morphology of the droplets was observed during the spreading phase within 3.00 ms, as illustrated in Figure 3a, and once the droplets began to spread in the direction of the texture and downstream (t = 3.08 ms, Figure 3b), their centers of gravity began to change transiently with the direction of motion.…”
Section: Coupling Effect Of the Translational Motion And Oriented Included Anglesupporting
confidence: 91%
“…However, the modification of the wetting dynamics by movement is reflected in the higher Weber number regime (We = 25.6). It can also be observed that the spreading and receding phases of the lamella were thinner downstream at a given time (see the right side of the dotted lines in Figure 3b and 3c), which corresponds reasonably well with the findings of previous studies 22,24 . No distinguishable morphology of the droplets was observed during the spreading phase within 3.00 ms, as illustrated in Figure 3a, and once the droplets began to spread in the direction of the texture and downstream (t = 3.08 ms, Figure 3b), their centers of gravity began to change transiently with the direction of motion.…”
Section: Coupling Effect Of the Translational Motion And Oriented Included Anglesupporting
confidence: 91%
“…Due to the huge number of applications involved, drop impact has been intensively studied in the past years as, for example, the modeling of the influence of the drop size on the time evolution of the dynamic contact angle and contact radii [6], the study of the transition between bounce/stick/splash of nanodroplets [7,8], the impact of nanodroplets on textured surfaces [9], droplet impact over inclined substrates studied experimentally [10] or by using molecular dynamics techniques [11], experimen-tal studies of drop impact over a moving substrate [12], etc. Given the strong deformation of the droplet during impact, especially for cases with relatively high impact velocities, the evaluation of the dynamic contact angle is not very accurate in comparison with the measurement of the contact diameter of the drop.…”
mentioning
confidence: 99%
“…The balance between the kinetic energy, capillary, and viscous forces ends the spreading process and the lamella eventually reaches a maximum wetting length, L w , at time, t max 23–25 ; afterwards the droplet recedes back toward the center of the impact point. The impact dynamics hence is defined by the interaction of this lamella with the surface and the surrounding gas, 26 which makes the surface properties to play an important role in controlling the impact dynamics 27,28 . Usually droplet impact physics is observed over laboratorial tests performed on stationary solid surfaces.…”
Section: Methodsmentioning
confidence: 99%